High-titer rheumatoid factor seropositivity predicts mediastinal lymphadenopathy and mortality in rheumatoid arthritis-related interstitial lung disease - Albina Tyker (Nature Portfolio, 2021)
Abstract Rheumatoid arthritis-related interstitial lung disease (RA-ILD) is a common connective tissue disease-related ILD (CTD-ILD) associated with high morbidity and mortality. Although rheumatoid factor (RF) seropositivity is a risk factor for developing RA-ILD, the relationship between RF seropositivity, mediastinal lymph node (MLN) features, and disease progression is unknown. We aimed to determine if high-titer RF seropositivity predicted MLN features, lung function impairment, and mortality in RA-ILD. In this retrospective cohort study, we identified patients in the University of Chicago ILD registry with RA-ILD. We compared demographic characteristics, serologic data, MLN size, count and location, and pulmonary function over 36 months among patients who had high-titer RF seropositivity (≥ 60 IU/ml) and those who did not. Survival analysis was performed using Cox regression modeling. Amongst 294 patients with CTD-ILD, available chest computed tomography (CT) imaging and serologic data, we identified 70 patients with RA-ILD. Compared to RA-ILD patients with low-titer RF, RA-ILD patients with high-titer RF had lower baseline forced vital capacity (71% vs. 63%; P = 0.045), elevated anti-cyclic citrullinated peptide titer (122 vs. 201; P = 0.001), CT honeycombing (50% vs. 80%; P = 0.008), and higher number of MLN ≥ 10 mm (36% vs. 76%; P = 0.005). Lung function decline over 36 months did not differ between groups. Primary outcomes of death or lung transplant occurred more frequently in the high-titer RF group (HR 2.8; 95% CI 1.1–6.8; P = 0.028). High-titer RF seropositivity was associated with MLN enlargement, CT honeycombing, and decreased transplant-free survival. RF titer may be a useful prognostic marker for stratifying patients by pulmonary disease activity and mortality risk.